Peran Patroli Roda Dua Satuan Sabhara Dalam Rangka Mengurangi Angka Pencurian Kendaraan Bermotor Di Polres Purwakarta - Joesteve Christian Fortuna (Police Studies Review, 2020)
This research is motivated by an increase in motor vehicle theft rates in Purwakarta Police Precinct. The Republic of Indonesia National Police make preventive efforts, one of which is by conducting patrol activities to prevent the occurrence of motor vehicle theft. Therefore, a study was conducted to find out about the role of two-wheeled Sabhara patrol units in Purwakarta Polres in order to reduce the number of motor vehicle theft in the Purwakarta Regency area, as well as to find out what factors hampered the implementation of Sabhara's two-wheeled sabhara patrol unit. The theory used is crime prevention theory and the theory of patrols about patrol. While the concept used is the concept of role, the concept of patrol, and the concept of two-wheeled patrol. The study was conducted with a qualitative approach, a type of descriptive survey research, data collection techniques used were interviews, document review, observation and research instrument sheets. The results of the study found the conclusion that the criminal acts of motor vehicle theft that occurred in Purwakarta Regency often occurred because of the many factors causing the crime. The negligence factor of the community as well as from the party of the criminal offender who committed the crime due to certain factors. In this case the role of the sabhara two-wheeled patrol unit is still not optimal and there are many shortcomings at each stage of the activity. The shortcomings regarding the implementation of the Sabhara two-wheeled patrol were not yet optimal. While the inhibiting factors of the role of two-wheeled patrols in carrying out their duties are Sarpras factors, personnel factors, personnel capability factors, and community factors. Research suggestions to maximize the role of the sabhara two-wheeled patrol unit (1) pay more attention to the sabhara two-wheeled patrol unit in Purwakarta Police Station, (2) Routine check about patrol task implementation, (3) give patrol member chance to finish vocational learning, (4) increase vacilities and equipment to patrol member